Governance and management of Takaful operators - Azahar, Muhamad Daniel Hakimi; Abusin, Mohammad Syirazi; Roseli, Mohamad Aiman; Mat, Muhammad (2025)
At the beginning, Takaful, an Islamic alternative to conventional insurance, plays a vital role in the Islamic financial system by providing risk protection in accordance with Shariah principles. Unlike traditional insurance, which is based on commercial risk transfer and profit-making from premiums, Takaful operates on the principles of mutual cooperation (ta'awun), shared responsibility, and voluntary contribution (tabarru). In recent years, the rapid growth of Islamic finance has underscored the need for robust governance frameworks tailored specifically to Islamic financial institutions, including takaful operators (Islamic insurance companies). Governance, as a vital component of any financial institution, ensures transparency, accountability, and ethical management, thereby safeguarding stakeholders’ rights and promoting sustainable development. However, within the Islamic finance sector, governance has historically received limited scholarly attention compared to areas like Islamic banking or capital markets. This gap presents a critical challenge, especially for takaful operators that serve a dual purpose: providing social welfare through takaful contracts while generating financial returns for shareholders. The introduction highlights that Takaful operators face specific challenges, such as conflicts of interest between shareholders and participants, as well as compliance with Sharia principles that prohibit elements like Riba (interest) and uncertainty (Gharar). To address these issues, there is a need for robust governance mechanisms that foster transparency, accountability, and stakeholder protection. However, the introduction points out that governance in Takaful is impacted by the nature of its contracts (wakalah, mudharabah, or hybrid), the composition of the board, and leadership roles. The leaders' seniority or entrenchment can influence how effectively governance mechanisms function, either strengthening or weakening their impact on performance. Overall, establishing sound governance tailored to Takaful's unique features is essential for ensuring its sustainability and stakeholder trust. (Sallemi, 2021)